The Influence of Criminal Norms in the New Criminal Code on Variations in Judges’ Decisions - Ghina Praska Levi; Fero Sanjaya; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
Sentencing disparity remains a persistent issue in criminal justice systems because judicial decisions in similar cases often produce significantly different outcomes. Indonesia’s criminal law reform through Law No. 1 of 2023 introduced more structured sentencing norms intended to improve consistency in judicial decisions. This study examines the influence of these norms on variations in judicial sentencing. The research uses a quantitative explanatory design with a comparative approach between periods before and after the enactment of the new Criminal Code. The dataset consists of legally binding court decisions on selected criminal offenses. Samples were selected using stratified random sampling based on case type and court jurisdiction. Data analysis employed descriptive statistics, independent t-tests, and multiple linear regression to evaluate the effect of normative reform on sentence length variation. The findings indicate a significant decrease in average sentence length after the implementation of the new sentencing norms. The standard deviation of sentences also declined, suggests reduced sentencing variation. Regression results show that the reform variable has a negative and statistically significant effect on sentence length, although its explanatory contribution remains limited. This study contributes to the literature by providing empirical evidence on how legislative reform influences voting practices in a developing legal system. Methodologically, it offers a comparative quantitative approach using court decision data to evaluate the impact of criminal law reform. Keywords :​ Penal norms, New Criminal Code, Variations in sentencing, Criminal disparities, Criminal law reform.